EXPLORATION OF THE DYNAMICS OF THE CHARACTERS' PSYCHOLOGY IN THE SHORT STORY "SHAHRAZAD" BASED ON THE PERSPECTIVE OF LITERARY PSYCHOLOGY: EKSPLORASI DINAMIKA KEJIWAAN TOKOH DALAM CERPEN “SYAHRAZAD” BERDASARKAN PERSPEKTIF PSIKOLOGI SASTRA - Fikri Haikal; Yola Oktavia; Muhammad Farihul Qulub (Muaddib: Journal of Arabic Language and Literature, 2026)
This study aims to analyze the psychological dynamics of the characters in the short story Syahrazad through a literary psychology approach. This approach is used to examine the psychological construction of the characters reflected in the narrative, particularly those related to inner conflict, motivation, traumatic experiences, and the expression of the characters' personalities throughout the story. This study uses a qualitative descriptive method with text analysis techniques as the main data source. The analysis focuses on the central characters and the psychological dynamics that influence their development in the story. The results show that the characters in the short story Syahrazad represent the complexity of emotions and psychological conditions characterized by ambivalence between hope and fear, courage and vulnerability. In addition, the use of symbolism, storytelling techniques, and the development of the storyline also strengthen the representation of the psychological dimensions of the characters in depth. These findings emphasize that literary works function not only as aesthetic products, but also as reflective media capable of representing human psychological dynamics in a subtle and profound manner.